2017
DOI: 10.1016/j.acra.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Search Strategies on Perceptual Performance

Abstract: Rationale and Objectives: Radiology expertise is dependent on the use of efficient search strategies. The aim of this study is to investigate the effect of teaching search strategies on trainee's accuracy in detecting lung nodules at computed tomography.Materials and Methods: Two search strategies, "scanning" and "drilling," were tested with a randomized crossover design. Nineteen junior radiology residents were randomized into two groups. Both groups first completed a baseline lung nodule detection test allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These combined results support the superiority of drilling vs. scanning strategies. It is also worth noting that, in contrast with of Drew et al (2013b) findings, none of the participants in the van der Gijp et al (2017b) study reported (or had eye movements suggestive of) ‘scanning’ when reading images under normal work conditions. This is consistent with one of the authors’(SW) experience.…”
Section: Eye Movements and Search Patterns In Radiologymentioning
confidence: 58%
See 1 more Smart Citation
“…These combined results support the superiority of drilling vs. scanning strategies. It is also worth noting that, in contrast with of Drew et al (2013b) findings, none of the participants in the van der Gijp et al (2017b) study reported (or had eye movements suggestive of) ‘scanning’ when reading images under normal work conditions. This is consistent with one of the authors’(SW) experience.…”
Section: Eye Movements and Search Patterns In Radiologymentioning
confidence: 58%
“…Whereas drillers had more experience than scanners in the above dataset (Drew et al, 2013b), a follow-up study showed that instruction in drilling techniques led to improved performance in residents, compared with instruction in scanning techniques (van der Gijp et al, 2017b). These combined results support the superiority of drilling vs. scanning strategies.…”
Section: Eye Movements and Search Patterns In Radiologymentioning
confidence: 99%
“…There are many examples of pattern recognition in medical image interpretation. Instant pattern recognition, for example, grew out of the cognitive psychology discourse, and offers the opportunity to compare medical imaging information with similar previous examples from memory (van der Gijp 2017). Other prominent examples of the application of pattern recognition include the ability to recognise abnormalities rather than to interpret findings based on a formal set of rules (Chen et al 2017), the 'description' of, for example, imaging appearances for professionals who require anatomic closure (Williams et al 2019), and how it is a form of 'non-systematic' reasoning so as to allow professionals to quickly look at whatever attracts their attention (Kok et al 2015).…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…First, a low-energy (LE) image is produced, which is similar to a plain mammogram, also known as a full-field digital mammogram (FFDM) (57). Subsequently, an additional, post-contrast image is produced, known as a recombined contrast-enhanced (RC) image (54,58). Both images are evaluated conjointly and comprise the CEM examination (54).…”
Section: Rq4 How Does the Longitudinal Development Of Visual Search Pmentioning
confidence: 99%
“…Therefore, the visual search component could be larger in the evaluation of volumetric images compared to two-dimensional images (57). Therefore visual search training on volumetric images may be more beneficial for novices compared to the results on two-dimensional images (58). However, chest radiographs and plain mammograms represent a substantial proportion of the radiology departments' workload (59) and are both considered difficult to master (60,61).…”
Section: Limitationsmentioning
confidence: 99%